The "Mask" and the Writing Mechanisms in the Contemporary Algerian Feminist Novel - Aichouna, Saida (Journal of Human Sciences, 2021)
With the emergence of  new awareness in the field of critique, the creative process adopted new standards that contributed to changing its features , and with the emergence of feminism in narrative and criticism, the woman writer tried to invest in the intellectual awareness to establish a different style of writing. The latter seeks to change the traditional linguistic system and to shake the inherited masculine norms according to an outlined program which is based on exposing the hidden and uncovering what is surrounded by silence. Accordingly, this study examines the problem of employing the "mask" in the Algerian feminist writing as it follows the strategies of the female writer in revealing male discourses that have been reinforced by authority and culture.